Consumption in Brazil : Where to Next? - Matheson, Troy (IMF Working Papers; Working Paper ;, 2017)
Private consumption has been a key driver of growth in Brazil for more than a decade. Over this time, Brazilian consumers have benefited from a favorable policy environment, a rapid phase of development-dramatically increasing economic, financial and social inclusion- and a supportive external environment. Meanwhile, infrastructure gaps have widened and investment and productivity levels have fallen behind. The consumption-led growth model now appears to have run its course. The prospect of a period of macroeconomic adjustment presents an opportunity to adjust policy settings to ensure stronger, more balanced and sustainable growth over the medium term.